IMPLEMENTASI KTSP PADA MATA PELAJARAN IPA DI SEKOLAH DASAR KELAYU KECAMATAN SELONG KABUPATEN LOMBOK TIMUR NTB TAHUN PELAJARAN 2007/2008 - Muhammad Sururuddin (Educatio, 2009)
This research aims to know the implementation of School-Based Curriculum on the subject of Natural Science in Kelayu State Elementary School, in the District of Selong. The focus of the research is to explore the obstacles and the supporting factors in implementing the school based curriculum. This study employs the descriptive-qualitative method. The subjects of the research are the principal, the teachers, and the students. The research data were collected by conducting observation, interviews, and documentation study and analyzed qualitatively using the analysis technique of Huberman. From the result of the research, the researcher finds some descriptions about the implementation of the school-based curriculum. (1) The four state elementary schools have imposed the school-based curriculum since the academic year of 2007/2008. (2) Each school has not had complete instruments for the school-based curriculum. (3) The obstacles encountered by the schools are that (a) they lack the main text-books and other supporting books and the laboratory equipment both for the teacher and for the students in learning activities, which is overcome by asking the teachers to provide handouts and to create simple laboratory Natural Science equipment through Teacher Working Group (KKG), (b) most teachers have not well understood the assessment system in the school-based curriculum, which is overcome by sharing teaching experience in  Teacher Working Group (KKG), (c) most teachers have not been accustomed to giving, correcting, and returning the homework to the students routinely, and (d) the students are not quite active in asking questions and expressing their opinions in the learning process. (4) The supporting factors in implementing the school-based curriculum are that (a) some schools have had complete equipment for laboratory practice of Natural Science to have the students understand the teaching materials easily, (b) the principal gives enough attention to the school-based curriculum and monitors the implementation of it, (c) complete sports facilities are available, and (d) the school environment is rich in the learning sources. In general, there are no different phenomena in the implementation of the school-based curriculum in the four state elementary schools in Kelayu such as South Kelayu Elementary School 1, South Kelayu Elementary School 2, North Kelayu Elementary School 1 and North Kelayu Elementary School 2  regarding the learning process, technical operation, and the availability of learning supporting facilities, whereas the most different factors in the four schools are found in the aspects of collaboration and internal culture of the schools.Keywords: The Implementation of (KTSP), Natural Science (IPA)